Structural and optical properties of PPO/PVP blended polymer film. (2022) - Harinkhere, Disha; Karma, Nikita; Choudhary, K.K.; Kaurav, Netram
Highlights: Spin coating method was used to make a PPO/PVP thin film. The PPO/PVP-based polymer film was found to be amorphous. Absorption peaks in the UV region at 311 nm and 367 nm. The optical band gap of the PPO/PVP film is 2.9eV. The Urbach energy of the PPO/PVP thin film was 0.294 eV. Abstract: In the present work, a polyphenylene oxide/Polyvinyl pyrrolidone (PPO/PVP) thin film has been synthesized by using a spin coating technique. The structural and optical properties of the thin film were studied by using X-ray diffraction and optical absorption spectroscopic techniques. The XRD results showed that precursor polymers PPO and PVP along with PPO/PVP-based polymer film exhibited amorphous behavior. Optical properties were obtained using UV–Vis spectroscopy. Two absorption peaks were identified in the UV area, at 311 nm and 367 nm, respectively, and the optical band gap of the PPO/PVP film was found at 2.9 eV. The synthesized PPO/PVP thin film had an Urbach energy of 0.294 eV, as per the findings.